12.21: Cyclic loading in stainless steel links under lateral loads. (13th September 2017) - Chacón, Rolando; Arrayago, Itsaso; Mirambell, Enrique; Real, Esther
ABSTRACT: Link elements are dissipative devices in form of beam segments that are typically included in eccentrically braced frames (EBF) subjected to lateral loads and seismic hazard. Studies related to short links, energy dissipation and plastic hinge formation have been presented for carbon steel elements with several conclusions at material, member and structural levels. Stainless steel is a nonlinear metallic material with particular appeal for its structural use due to a considerable amount of capabilities such as corrosion resistance, circular life‐cycle, sustainability, strength, ductility and aesthetics. Despite the increase of the use of stainless steel for structural elements in construction, the behaviour of this material for structural purposes is not defined accurately as the carbon steel in all applications. The most important difference between these types of steel is the shape of the stress‐strain curve. Whereas carbon steel typically exhibits linear elastic behaviour up to the yield stress and a plateau before strain hardening is encountered, stainless steel has a more rounded response with no well‐defined yield stress, leading to a non‐linear material behaviour. The elastic stiffness, maximum load, shear deformation capacity as well as the energy dissipation in short links are generally affected by the defined geometrical parameters such as link length, web stiffening and connectivity. Due to the material nonlinearity of stainless steel, this influence may be considerably affected by the stress‐strain curve and its corresponding energy dissipation since a nonlinear kinematic hardening branch must be adequately provided in numerical simulations for the sake of accurately reproducing the cyclic behaviour. In this paper, a numerical model aimed at studying the cyclic behaviour of short stainless steel links subjected to seismic lateral loads is presented. The model accounts for the material and the geometrical nonlinearities. Several geometrical as well as material configurations (length, web stiffening and constitutive equations) are studied. The results and conclusions obtained in this research are used for a subsequent definition of a research program related to stainless steel frames subjected to seismic loading including several structural configurations in both concentrically (CBF) and eccentrically (EBF) braced frames assembled with plastic or slender members.